Atividades educativas na rede de saúde na perspectiva da política nacional de educação permanente - Maia, Ludmila Grego (2014)
The normative processes of formal organizations for the training of the human resources in the Brazilian Unified Health System (SUS) indicate that there are different conceptions of healthcare education, where terminologies such as continuing education and permanent healthcare education have coexisted in the same space of time as educative processes, sometimes being a confusing factor in the imaginary of the professionals. The implementation of the National Policy of Permanent Healthcare Education (NPPHE) defined these processes as learningwork and by occurring in the people’s everyday lifeand organizations. The goal of this work was to analyze the records of the educational activities performed by the healthcare units of the municipality of Jataí from the perspective of NPPHE. It was decided for a descriptive study, retrospective with documental analysis of the activities described in 2012. The results pointed out that the educative activities in the municipality have been mostly related to the healthcare education, focused on community, with demand and internal events to the unity, followed by the continuing education activities for specific groups. The number of activities focused on the worker was of 8,4% in relation to the universe of study. The justifications for them to happen departed from two categories: administrative issues and health care. Therefore, the effective implementation of the permanent healthcare education is a challenge for the healthcare services, by considering the pedagogical-political complexity in which falls the context of the public health in Brazil. Moreover, to manage the change of educative practices which are significant at work for work, one requires a continuous professional training.